A Study of Polystyrene-Metal Powder Conductive Composites - Iqbal, MZ; Mamoor, GM; Bashir, Tariq; Irfan, MS; Manzoor, MB (Journal of Chemical Engineering, 2011)
Conductive polymer composites were prepared from polystyrene as the base material and utilizing different metallic fillers by melt processing technique using a Brabender ® plasticorder at 230°C and 120 RPM spindle speed. Different fillers used include nickel powder, carbon black, Iron and copper powders of one micron sizes. Samples for tensile, thermal and resistivity testing were prepared from hydraulic press under 220 bar pressure, at 220°C for 5 minutes and then cooling to atmospheric temperature. Iron based polystyrene composite showed good mechanical properties and nickel based composite showed better thermal and conductive properties. Three kinds of treating agents were used to modify iron which includes wax, stearic acid and acetic acid. Iron treated with acetic acid composites showed improvement in electrical and mechanical properties. This improvement was attributed to the chemical linkage established between acetic acid and polystyrene at the processing temperatures. Keywords conductive composite; fillers; polystyrene; metal DOI: 10.3329/jce.v25i0.7240 Journal of Chemical Engineering, IEB Vol. ChE. 25, No. 1, December 2010 pp.61-64